Pengaruh Persepsi Kampus Program Mengajar, Lingkungan Keluarga, dan Kondisi Ekonomi Keluarga terhadap Minat Menjadi Guru - Irawan, Fredi; Pujiati, Pujiati; Suroto, Suroto; Marsaid, Nurdin (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The Faculty of Teacher Training and Education, University of Lampung is one of the faculties that produces student output as teachers. Students must have an interest in becoming a teacher when they have graduated from the Faculty of Teacher Training and Education, University of Lampung. Therefore, this study aims to determine the effect of Perceptions of the Teaching Campus Program (KM), Family Environment, and Family Economic Conditions on interest in becoming a teacher in FKIP students at the University of Lampung. This research was conducted using a survey method with a quantitative approach. The total population in this study was 112 students. The sampling technique used is simple random sampling, which is 88 samples. The data were tested using partial analysis (t test) and simultaneously (f test). The results of the research hypothesis indicate that there is a partial and simultaneous influence on the perception of campus teaching programs, family environment and family economic conditions on interest in becoming a teacher in FKIP students at the University of Lampung. The results of this study are expected to be a reference in learning, especially to increase interest in becoming a teacher for FKIP students at the University of Lampung.